Describe su juguete preferido - Silva Bazan, Nancy (2019)
The present learning demonstration session "Describing your favorite toy", for boys and girls of 3 years in regular basic education, which competence learning purpose: Build his identity, combining skills like, value himself, self-regulation of his emotions. At the same time, it responds to the performance “Recognizes his needs, sensations, interests and preferences; differentiates them from others through words, actions, gestures or movements. Consequently, it assumes a socio-constructivist pedagogical position within the framework of the competence curriculum, configured with the didactic processes of the person-social area and oriented with the formative evaluation within the intercultural humanism paradigm that promotes the Peruvian state.